Genetic basis of resistance waves among methicillin resistant Staphylococcus aureus isolates recovered from milk and meat products in Egypt - Ammar, A M; Attia, A M; Abd El-Hamid, M I; El-Shorbagy, I M; Abd El-Kader, S A (Cellular and Molecular Biology, 2016)
Antimicrobial resistance of methicillin-resistant Staphylococcus aureus (MRSA) poses a serious problem for clinicians worldwide. The present study attempted to evaluate the susceptibility patterns of MRSA to various antimicrobials and the prevalence of inducible clindamycin resistance as well as the relevant antibiotic and antiseptic resistance genes among these isolates. Totally, 40 MRSA isolates were recovered from examined milk and meat product samples (18.60%). Multi-drug resistance (MDR) was remarkably observed among 85% of these isolates. There was a good correlation between phenotypic determination of methicillin, amoxicillin/clavulinic acid and tetracycline resistances and PCR detections of mecA, blaZ and tet(K) genes, respectively, but norA gene was not detected in the four ciprofloxacin resistant isolates. Although, 55% of MRSA expressed resistance to benzalkonium chloride (BC), neither qacA/B nor smr gene was detected. Of 20 isolates exhibiting erythromycin- clindamycin discordant resistance pattern, 8 displayed positive double disk diffusion (D-zone) test denoting inducible macrolide-lincosamide-streptogramin B (MLSB) resistance phenotype with the inducibly expressed erm(A) and erm(C) genes in 87.5% of these isolates. Besides, the remaining 12 isolates showed MS phenotype (resistant to macrolides and type B streptogramins only) with a variety of erm(A), mph(C), msr(A) or a combination of these genes including erm(C). Finally, the constitutive MLSB phenotype with the constitutive expression of erm(A), erm(B) and erm(C) genes was comprised in 2 isolates with higher minimum inhibitory concentration (MIC) values for erythromycin (512 and 1024 µg/ml) and clindamycin (16 and 32 µg/ml). These findings suggested the importance of monitoring the evolution of MRSA resistance.